Association between haemoglobin level and all-cause mortality in haemodialysis patients: the link with inflammation and malnutrition - Selim, G; Stojcheva Taneva, O; Sikole, A; Amitov, V; Trajcheska, L; Asani, A; Trojacanec-Piponska, S; Polenakovic, M (Macedonian Academy of Sciences and Arts, 2007)
Although anaemia management has improved in haemodialysis (HD) patients in recent years, many of them still have haemoglobin (Hb) levels below the current recommendations. The consequent anaemia could be one of the links between malnutrition and inflammation, and higher mortality in HD patients. The study objective was to determine the relationship between Hb levels and outcome in patients undergoing HD, accounting for inflammation and malnutrition. We retrospectively analysed a total of 236 patients on HD between January 2003 and December 2005, classified by absence or presence of inflammation and malnutrition (defined as serum albumin levels < 40 g/L and CRP > 8mg/l). Serum levels of Hb, ferritin, creatinine, cholesterol, triglycerides, HDL (high-density lipoprotein cholesterol), LDL (low-density lipoprotein cholesterol), albumin and CRP were measured monthly, fibrinogen was measured every third month. Over the period of three years, 73 out of 236 patients (30%) had died, most from cardiovascular diseases (62%). Presence of inflammation and malnutrition (in 44% of patients) was associated with older age (60.69 -/+ 12.46 vs. 54.52 -/+ 12.37, p = 0.0002), lower levels of Hb (99.53 -/+ 14.97 vs. 111.86 -/+ 10.38 g/l, p = 0.0000), creatinine (835.88 -/+ 179.84 vs. 1069.98 -/+ 821.23-/+mol/l, p = 0.0047), albumin (36.58 -/+ 3.41 vs.40.32 -/+ 2.82 g/l, p = 0.0000), cholesterol (4.32 -/+ 1.04 vs. 4.75 -/+ 1.09 mmol/l, p = 0.0025) and higher levels of fibrinogen (4.94 -/+ 1.18 vs. 4.29-/+0.91g/l, p=0.0000) and CRP (30.42-/+29.47 vs. 5.24-/+4.89 mg/l, p=0.0000). The Kaplan-Meier analysis showed that, irrespective of the absence or presence of inflammation and malnutrition, the all-cause mortality was higher in patients with Hb <110g/l (Log-Rank, p=0.00147; p=0.00222). On the other hand, Kaplan-Meier showed that, irrespective of the absence or presence of anaemia (Hb > 110g/l and Hb < 110g/l), the all-cause mortality was higher in patients with the presence of inflammation and malnutrition (Log-Rank, p=0.00222; p=0.00263). The Cox proportional hazard analysis, adjusting for age, showed that only lower serum levels of Hb and higher CRP were associated with all-cause mortality (chi-square=110,306, p=0.0000). Our findings confirm the association of Hb levels < 110g/L with higher mortality among maintenance HD patients, especially in patients with the presence of inflammation and malnutrition. Further investigation of the relationships among anaemia, inflammation and malnutrition and survival is warranted.